Measurement of electron-phonon interaction time of niobium using heating effect in SIS tunnel junction - Tan, B; Yassin, G; Kittara, P; Leech, J (National Radio Astronomy Observatory, 2009)
The heating of SIS tunnel junctions by local oscillator (LO) power and bias voltage is well known and has been reported previously. In this paper, we present a novel method for recovering the heating parameters from the experimental pumped I-V curves of an SIS device at 700 GHz, together with the coupled LO power and the embedding impedance. Since this is obtained without assuming a particular power law between LO power and junction temperature, we will be able to find τeph, the electron-phonon interaction time of the superconducting material at various bath temperatures. We would deduce a power law that describes the dependence of the heat flow equation on temperature.